(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2020)
The potential for development in the Arctic Circle is wide and it is fully predictable that the development of resources in the region will accelerate further exploration of the Arctic sea route. Russia is showing high interest in developing resources that are not in the economic sanction list. Moreover, the exploration and utilization of the so-called Arctic sea route across the regional ocean is recently receiving massive attention along with the climate change. Korea and Russia have expanded the economic cooperation and now the two countries are looking for a new model of the work. They can share the goals through the further development of Russian Arctic Circle with the rapid exploitation of resources due to climate change and technological development. Korean companies have begun to bring the real economic benefits, having positive effects on related industries such as the construction of transport and special ships. There are many ways for realizing the goal, but we can specifically propose a Korea-Russia FTA. In the process of pursuing it, the government should also consider various tasks, such as harmonizing with the FTAs Korea has been signing, and dealing with the domestic law in accordance with the new FTA, based on the previous experiences. From Russia’s point of view, special circumstances such as the EAEU should be taken in consideration. The process of signing the FTA, which will serve as the international legal basis for cooperation between the partners, should be clearly marked for the purpose of ‘Sustainable Arctic Development’. Furthermore, these propositions should be able to be digested in the process of utilizing FTAs and readjusting domestic and international regulations, as well as the joint respond to the emergence of new industries, markets, and even unforeseen issues. In Korea’s perspective, it should consider the possibility that the FTA could be used in non-economic areas such as on the Korean Peninsula issue. Key words: Korea, Russia, Arctic Circle, Arctic Sea Route, Free Trade Agreement (FTA), Eurasian Economic Union (EAEU).